Răspuns :
inmultim prima ecuatie cu 2 =>
4a+2b=6
-4a+b=5
____________
3b=11
b=11/3 => 4a+2x11/3=6
4a+22/3=6
4a=6-22/3 (amplificam cu e )
12a=18/3-22/3 (am scapat de numitor)
12a=-4/3
a=-4/3 / 12
a=-1/9
4a+2b=6
-4a+b=5
____________
3b=11
b=11/3 => 4a+2x11/3=6
4a+22/3=6
4a=6-22/3 (amplificam cu e )
12a=18/3-22/3 (am scapat de numitor)
12a=-4/3
a=-4/3 / 12
a=-1/9
-4a +b =5 -4a + b =5
2a +b = 3 / · 2 4a + 2b = 6
--------------------
/ 3b = 11 ; b = 11 /3
2a + 11 /3 = 3 / · 3
6a + 11 = 9
6a = 9 -11
6a = -2
a = -1/3
2a +b = 3 / · 2 4a + 2b = 6
--------------------
/ 3b = 11 ; b = 11 /3
2a + 11 /3 = 3 / · 3
6a + 11 = 9
6a = 9 -11
6a = -2
a = -1/3